SOCIAL IDENTITY, LANGUAGE POLITICS AND EDUCATION POLICY IN JAMMU AND KASHMIR: A CASE STUDY (International Journal of Food and Nutritional Sciences, 2021)
AbstractThe core concept of this study is that Education should not be seen as a neutral and apolitical field. Rather, it should be understood as a political act that involves power dynamics in society. To achieve this, research in Education and about the conflicts arising out of power dynamics in society should be conducted actively. At the core of the political conflict is the Kashmiri social identity that has acquired salience in a temporally graded manner. An expression of the Kashmiri social identity has been in the form of dissent against the Indian State. Alternative expressions of the same through language politics form a link through which education policy in the state can be studied relationally. This link between social identity, language politics and their combined influence on education policy forms the core of this study.